Cut to the chase: a review of CD26/dipeptidyl peptidase‐4's (DPP4) entanglement in the immune system. (13th May 2016) - Klemann, C.; Wagner, L.; Stephan, M.; von Hörsten, S.
Summary: CD26/DPP4 (dipeptidyl peptidase 4/DP4/DPPIV) is a surface T cell activation antigen and has been shown to have DPP4 enzymatic activity, cleaving‐off amino‐terminal dipeptides with either L‐proline or L‐alanine at the penultimate position. It plays a major role in glucose metabolism by N‐terminal truncation and inactivation of the incretins glucagon‐like peptide‐1 (GLP) and gastric inhibitory protein (GIP). In 2006, DPP4 inhibitors have been introduced to clinics and have been demonstrated to efficiently enhance the endogenous insulin secretion via prolongation of the half‐life of GLP‐1 and GIP in patients. However, a large number of studies demonstrate clearly that CD26/DPP4 also plays an integral role in the immune system, particularly in T cell activation. Therefore, inhibition of DPP4 might represent a double‐edged sword. Apart from the metabolic benefit, the associated immunological effects of long term DPP4 inhibition on regulatory processes such as T cell homeostasis, maturation and activation are not understood fully at this stage. The current data point to an important role for CD26/DPP4 in maintaining lymphocyte composition and function, T cell activation and co‐stimulation, memory T cell generation and thymic emigration patterns during immune‐senescence. In rodents, critical immune changes occur at baseline levels as well as after in‐vitro and in‐vivo challenge. In patients receiving DPP4 inhibitors, evidence of immunological side effects also became apparent. The scope of this review is to recapitulate the role of CD26/DPP4 in the immune system regarding its pharmacological inhibition and T cell‐dependent immune regulation.